The Winchcombe Meteorite: one year on. Issue 1 (1st February 2022) - O'Brien, Áine Clare; Pickersgill, Annemarie; Daly, Luke; Jenkins, Laura; Floyd, Cameron; Martin, Pierre-Etienne; Hallis, Lydia Jane; King, Ashley; Lee, Martin
Abstract : It was the first UK meteorite fall for 30 years. Here we gather the story of a remarkable community hunt involving pandemic precautions, social media spikes and some very lucky guinea pigs. Abstract: It was the first UK meteorite fall for 30 years. Here we gather the story of a remarkable community hunt involving pandemic precautions, social media spikes and some very lucky guinea pigs.